Development of Virtual Laboratory in Physics Subject for Senior High School Phase-F - Maharini Rizky Pratiwi; Ramalis Hakim; Zelhendri Zen; Rayendra; Fetri Yeni J; Jodi Hardika (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop a valid, practical, and effective virtual laboratory as a solution to overcome limitations in physics education, with the expectation of improving both teaching quality and students' understanding of physics concepts. The research follows a Research and Development (R&D) approach using the 4-D model, which includes four stages: define, design, develop, and disseminate. The subjects of this study were 28 Phase-F students at SMA Negeri 11 Padang. The results include a virtual laboratory for Phase-F high school physics, validated with high scores: 89% for content validity, 97% for media validity, and 92% for language validity, all categorized as highly feasible. The trial for practicality among students scored 80.39%, categorized as practical, while the teacher trial scored 97%, categorized as highly practical. The effectiveness test showed significant improvement in student performance, with the average score increasing from 38.39 to 79.64. The N-gain score was 0.67, indicating moderate improvement. Based on the development and trials, it can be concluded that the virtual laboratory product for Phase-F high school physics is valid, practical, and effective for use in learning activities.